2019
DOI: 10.5114/ceji.2019.84010
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of elicited soybean (Glycine max) extract on Balb/C mice (Mus musculus) with high-fat and -fructose diet

Abstract: Obesity causes adipocyte hypertrophy, which leads to cell death. Consequently, macrophages and lymphocytes infiltrate into the adipose tissue and elevate pro-inflammatory cytokine production through TLR activation. This study aimed to determine the efficacy of soybean extract, which was elicited by Saccharomyces cerevisiae and light, as an anti-inflammatory agent in mice with a high-fat and -fructose diet (HFFD). The elicited soybean extract (ESE) was administered orally to mice for four weeks after being give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Studies demonstrated by Nur’aini et al. demonstrated that ESE administration suppressed the proinflammatory mediators expressed by CD4 and CD8 T cells [ 56 ]. These findings are consistent with our present result, in which the inhibition of CD11c + activity is followed by the restoration of naïve T cells after ESE administration ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated by Nur’aini et al. demonstrated that ESE administration suppressed the proinflammatory mediators expressed by CD4 and CD8 T cells [ 56 ]. These findings are consistent with our present result, in which the inhibition of CD11c + activity is followed by the restoration of naïve T cells after ESE administration ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, various functionalities of black soybeans and adzuki beans have been reported. The ethanolic extracts of black soybeans, for instance, exerted notable antioxidant, anti-inflammatory, antinociceptive, and antiplatelet activities [ 16 , 17 , 18 ]. In addition, adzuki bean ethanolic extracts attenuated angiogenesis, diabetes, osteoporosis, muscle atrophy, and allergic inflammation, as well as delay in the progression of Alzheimer’s disease [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Saccharomyces cerevisiae and light act synergistically to enhance quadrupled glyceollin synthesis (Atho'illah et al 2017). Glyceollin is beneficial to health; it acts as an antioxidant (Kim et al 2011), has anti-inflammatory properties (Atho'illah et al 2018;Nur'aini et al 2019), improves erythroid progenitor capacity (Safitri et al 2017), and maintains the hematopoietic system (Safitri et al 2018).…”
Section: Introductionmentioning
confidence: 99%